Artificial Insemination (AI) by Raw Semen: its Advantages and Disadvantages in Deshi Chicken (Gallus domesticus) - Das, S.K.; Adhikary, G.N.; Islam, M.N.; Paul, B.K.; Das, G.G. (International Journal of Poultry Science, 2004)
To judge the advantages and disadvantages of Artificial Insemination (AI) by raw semen in deshi chicken a test experiment was conducted in Bangladesh Agricultural University (BAU) poultry farm, Mymensingh, Bangladesh. Male birds (RIR) were collected from the BAU poultry farm, whereas the female birds (deshi hens) were purchased from nearby local village market. Both types of birds were kept in individual cage with adlibitum food and water and were given abdominal massage at least for three days (at the same time of the day) prior to AI. Collected semen was inseminated (0.20-0.25 ml/hen) directly by soft dropper into the female genital tract. The result of the present experiment showed that 1-2 females could be covered by semen collected from single ejaculate from one cock. It was also found that very small amount of semen was wastage by container. Thus it can be concluded that AI by raw semen is not profitable (except experimental point of view) until we use semen diluents for commercial purpose.